Cortical Surface Thickness in the Middle-Aged Brain with White Matter Hyperintense Lesions - Zhuang, Ying; Zeng, Xianjun; Wang, Bo; Huang, Muhua; Gong, Honghan; Zhou, Fuqing (Frontiers in Aging Neuroscience, 2017)
Background and purpose:Previous voxel-based morphometry studies have suggestedthatcortical atrophyis regionally distributedin middle-aged subjects with white matter hyperintense (WMH) lesions. However, few studies have assessed cortical thickness in middle-aged WMH subjects. In this study, we examined cortical thickness as well as cortical morphometryassociated with the presence ofWMH lesion load in middle-aged subjects. Participants and methods: Thirty-six middle-aged subjects with WMH lesions (WMH group) andwithoutclinicalcognitive impairment,and 34 demographically matched healthy control subjects (HCS group) participated in the study. Cortical thickness was estimated using an automated Computational Anatomy Toolbox (CAT12)as the distance between the gray-white matter border and the pial surface. Individual WMH lesions were manuallysegmented,and WMH loadswere measured.Statistical cortical maps were created to estimate differences incortical thickness between groupsbased on this cortex-wide analysis. Therelationship between WMH lesion loads and cerebral cortical thickness was also analyzed in CAT12. Results: Cortical thicknesswas significantly lowerin the WMH group than in the controls in multimodal integration regions, including the right and left dorsal anterior cingulate cortex (dACC), right and left frontal operculum (fO), right and left operculum parietale (OP), right and left middle temporal gyrus (MTG), and left superior temporal gyrus (STG)(P<0.01, family-wise error-corrected). Additionally, cortical thickness was also lowerin the recognition regions that contained the right temporal pole (TP), the right and left fusiform gyrus, and the left rolandic operculum (RO) (P<0.01, family-wise error-corrected). The results revealed that in the left superior parietal lobule (SPL),cortical thickness was higher in the WMH group than in the HCS group (P<0.01, family-wise error-corrected). A voxel-wisenegative correlation was found between cortical thickness and WMH lesion loads in the rightorbitofrontal cortex (OFC), right dorsolateral prefrontal cortex (DLPFC), and right subcallosal cortex (P<0.01, family-wise error-corrected). Conclusion: The main findings of this study suggest that middle-aged WMH subjects are more likely to exhibit cortical thinning,especiallyin multimodal integration and recognition- and motor-related regions.The current morphometry data provide further evidence for WMH-associated structural plasticity.